Cognitive Deficits Underlying Error Behavior on a Naturalistic Task after Severe Traumatic Brain Injury - Hendry, Kathryn; Ownsworth, Tamara; Beadle, Elizabeth; Chevignard, Mathilde P.; Fleming, Jennifer; Griffin, Janelle; Shum, David H. K. (Frontiers in Behavioral Neuroscience, 2016)
People with severe traumatic brain injury (TBI) often make errors on everyday tasks that compromise their safety and independence. Such errors potentially arise from the breakdown or failure of multiple cognitive processes. This study aimed to investigate cognitive deficits underlying error behavior on a home-based version of the Cooking Task (HBCT) following TBI. Participants included 45 adults (9 females, 36 males) with severe TBI aged 18-64 years (M = 37.91, SD = 13.43). Participants were administered the HBCT in their home kitchens, with audiovisual recordings taken to enable scoring of total errors and error subtypes (Omissions, Additions, Estimations, Substitutions, Commentary/Questions, Dangerous Behavior, Goal Achievement). Participants also completed a battery of neuropsychological tests, including the Trail Making Test, Hopkins Verbal Learning Test-Revised, Digit Span, Zoo Map test, Modified Stroop Test and Hayling Sentence Completion Test. After controlling for cooking experience, greater Omissions and Estimation errors, lack of goal achievement and longer completion time were significantly associated with poorer attention, memory and executive functioning. These findings indicate that errors on naturalistic tasks arise from deficits in multiple cognitive domains. Assessment of error behavior in a real life setting provides insight into individuals’ functional abilities which can guide rehabilitation planning and lifestyle support.